2021
DOI: 10.1002/app.51312
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient dye‐sensitized solar cells: A comparative study with two different system of solvent‐free binary room‐temperature ionic liquid‐based electrolytes

Abstract: In this work, novel redox electrolytes based on poly (ethylene oxide) (PEO) were prepared using binary ionic liquid 1‐methyl‐3‐propylimidazolium iodide (MPII) with 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI) or 1‐butyl‐3‐methylimidazolium tetrafluoroborate (BMIMBF4) to reduce the high viscosity of MPII. The addition of low viscosity ionic liquids is to overcome the low mass transportation of redox mediator faced by the single ionic liquid. Therefore, different ratios of ionic liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…6 In general, most gel electrolytes have low mechanical strength and tensile capacity, and mechanical properties often cannot be combined with ionic conductivity. 7,8 Therefore, the preparation of gel electrolytes with integrated properties remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In general, most gel electrolytes have low mechanical strength and tensile capacity, and mechanical properties often cannot be combined with ionic conductivity. 7,8 Therefore, the preparation of gel electrolytes with integrated properties remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal electrolyte for flexible and wearable electrochemical energy devices is anticipated to meet the requirements of multiple properties including high ionic conductivity, enough mechanical strength, wide electrochemical window, good thermal stability, and other attractive features, such as self-healing properties . In general, most gel electrolytes have low mechanical strength and tensile capacity, and mechanical properties often cannot be combined with ionic conductivity. , Therefore, the preparation of gel electrolytes with integrated properties remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazolium-based ionic liquids have been widely used as electrolyte components for lithium-ion batteries, [18,19] DSSCs, [20,21] supercapacitors [22,23] and field effect transistors [24,25] due to their low viscosity, [26,27] high conductivity, [28,29] non-flammability [30] and ease of functionalization through the available 1,3-positions. Regarding the conductivity of the ILs, it has been reported that oxygen atoms on the side chains of cation provide relatively higher conductivity values compared to the ones with the same length of n-alkyl chains due to ion-ion and van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a high cell efficiency, an organic solvent must be incorporated into the formulation of the electrolyte [19]- [21]. According to recent studies [22], the ionic liquid compounds that are incorporated in DSSCs can be used to obtain high efficiency. C4 to C10 alkyl chains will form compounds with ionic liquids (ILs) characteristics, while compounds with longer alkyl chains than that will form liquid crystals [23].…”
Section: Introductionmentioning
confidence: 99%